Two New Polyphenol Oxidase Genes of Tea Plant (Camellia sinensis) Respond Differentially to the Regurgitant of Tea Geometrid, Ectropis obliqua - Chen Huang (International Journal of Molecular Sciences, 2018)
Polyphenol oxidases (PPOs) have been reported to play an important role in protecting plants from attacks by herbivores. Though PPO genes in other plants have been extensively studied, research on PPO genes in the tea plant (Camellia sinensis) is lacking. In particular, which members of the PPO gene family elicit the defense response of the tea plant are as yet unknown. Here, two new PPO genes, CsPPO1 and CsPPO2, both of which had high identity with PPOs from other plants, were obtained from tea leaves. The full length of CsPPO1 contained an open reading frame (ORF) of 1740 bp that encoded a protein of 579 amino acids, while CsPPO2 contained an ORF of 1788 bp that encoded a protein of 595 amino acids. The deduced CsPPO1 and CsPPO2 proteins had calculated molecular masses of 64.6 and 65.9 kDa; the isoelectric points were 6.94 and 6.48, respectively. The expression products of recombinant CsPPO1 and CsPPO2 in Escherichia coli were about 91 and 92 kDa, respectively, but the recombinant proteins existed in the form of an inclusion body. Whereas CsPPO1 is highly expressed in stems, CsPPO2 is highly expressed in roots. Further results showed that the expression of CsPPO1 and CsPPO2 was wound- and Ectropis obliqua-induced, and that regurgitant, unlike treatment with wounding plus deionized water, significantly upregulated the transcriptional expression of CsPPO2 but not of CsPPO1. The difference between regurgitant and wounding indicates that CsPPO2 may play a more meaningful defensive role against E. obliqua than CsPPO1. Meanwhile, we found the active component(s) of the regurgitant elicited the expression of CsPPO may contain small molecules (under 3-kDa molecular weight). These conclusions advance the understanding of the biological function of two new PPO genes and show that one of these, CsPPO2, may be a promising gene for engineering tea plants that are resistant to E. obliqua.